First results of compact coherent Doppler wind lidar and its validation at IITM, Pune, India. (14th August 2013) - Devara, P. C. S.; Jaya Rao, Y.; Sonbawne, S. M.; Manoj, M. G.; Dani, K. K.; Saha, S. K.
ABSTRACT A coherent Doppler wind lidar was installed in July 2009 at the Indian Institute of Tropical Meteorology (IITM), Pune (18 ° 43 ′ N, 73 ° 51 ′ E, 559 m AMSL), India, to map the daily three‐dimensional wind fields in the atmospheric boundary layer (ABL). The aim was to provide a more in‐depth understanding of weather, climate and air quality over Pune initially and later to be extended to other suitable sites in the country. The excellent performance of the system led to the deployment of next generation (extended) wind lidar with higher pulse power (∼100 µJ) in July 2010 to probe winds in clear‐air (aerosol particles as tracers) as well as in cloud‐air (cloud particles as tracers) up to about 12 km AMSL. In this communication, a brief description of these two lidar versions together with some salient results, including comparison with co‐located in situ techniques is presented. Sample data obtained on some typical experimental days with extended lidar and its calibration with co‐located AWS and GPS Radiosonde are also presented. This comparison shows a reasonable agreement within the measurement accuracies. The spectral analysis of data reveals short‐period, propagating‐type gravity waves of about 5 min periodicity, exchanging energy between lower and upper altitude levels. In addition to the ABL evolution and Low Level Jet (LLJ) features, the data can be used to establish cirrus cloud structures and associated circulation.